Conceptualising climate – how public understanding of weather and climate influences perceptions of climate change globally - Brook, Adam (2020)
Although there is a growing body of literature exploring influences on public perceptions of climate change, little work has focused on how levels of conceptual understanding of deep time, namely the difference between weather and climate influence these perceptions. An online survey was distributed globally for the first time and used to measure respondents’ levels of conceptual understanding of weather and climate and perceptions of the risks associated with climate change. Data was also gathered on respondent media trends to identify any key sources of information on climate change for respondents. 669 completed questionnaires were received with respondents being globally dispersed across 62 nations. Results were analysed to evaluate the relationship between the levels of conceptual understanding of weather and climate and concern with climate change amongst respondents. Analysis was also completed to assess how the media influences this relationship. Results were presented for the Full Population (n=669) as well as regionally across European (n=303), North American (n=142), South American (n=20), African (n=57), Asian (n=99) and Oceania (n=44) response populations. The results show little variation exists between levels of conceptual understanding of weather and climate and perceptions of climate change across all populations, despite a significant knowledge gap existing between perceived and actual levels of conceptual understanding of weather and climate. This challenges previous research which has demonstrated a link between levels of conceptual understanding and perceptions of the risks posed by climate change. The results did demonstrate a relationship exists between respondents demonstrating ‘Very Low’ or ‘Low’ levels of conceptual understanding of weather and climate and relying on social media for the majority of information on climate change. The results establish the salience of clear communication online to educate the public on the difference between weather and climate is key to improve levels of conceptual understanding. This research corroborates the findings of a large body of existing literature that global levels of concern with climate change are high. The results also show respondents who demonstrate high levels of scepticism around the risks posed by climate change do not consider the long term effects of climate change to be significant, despite demonstrating high levels of agreement with the scientific consensus on the anthropogenic causes of climate change. The effects of the concept of psychological distance on influencing perceptions of climate change risk were also observed. Respondents who identified changes to their local environment were found to significantly correlate with levels of concern with climate change though no relationship was identified between levels of conceptual understanding of weather and climate and this effect.